A new family of Polak-Ribiere-Polyak conjugate gradient method with the strong-Wolfe line search - Mustafa, Mamat; Ghani, N.H.A.; Rivaie, M (2017)
Conjugate gradient (CG) method is an important technique in unconstrained optimization, due to its effectiveness and low memory requirements. The focus of this paper is to introduce a new CG method for solving large scale unconstrained optimization. Theoretical proofs show that the new method fulfills sufficient descent condition if strong Wolfe-Powell inexact line search is used. Besides, computational results show that our proposed method outperforms to other existing CG methods.